Entrepreneurship development and pedagogical gaps in entrepreneurial marketing education. Issue 2 (July 2020) - Amjad, Tayyab; Abdul Rani, Shamsul Huda Binti; Sa'atar, Shiza Binti
Abstract: In the age of automation and artificial intelligence, the need for sustainable entrepreneurship for job creation has significantly raised. For the development of sustainable entrepreneurship in recent years, business schools worldwide have recognised their roles, and started providing entrepreneurship education (EE). Due to being in emerging phase, the EE at business schools is following pedagogic approaches that are not exclusively developed for entrepreneurship, and hence, not suitable with the practical entrepreneurial needs. This leaves graduates lacking in many types of entrepreneurial skill-sets. One of those key skill-sets is entrepreneurial marketing (EM), which is one of the most dominating problems for SME entrepreneurs for the survival and growth of their businesses. Furthermore, the literature highlights that lack of EM skill-set is also one of the leading causes of entrepreneurial failure. The failure of SME entrepreneurs not only discourages them, but also damages the initiatives taken by the governments and private institutions for entrepreneurship development in the economies. Thus, considering the critical importance of EM education for the development of entrepreneurship, this paper has highlighted the pedagogical gaps in EM education, proposed future research avenues, and made practical implications for business schools' academic authorities to upgrade their pedagogical models.